ISOLATION OF LIPASE PRODUCING FUNGI FROM GROUNDNUT OIL MILL EFFLUENT SOIL SITE AT NANDYAL - A.PRAVEEN KUMAR; K.JAYA KUMAR; G.NARASIMHA (International Journal of Pharma and Bio Sciences, 2012)
The study is attempted to investigate the production of potent lipase from groundnut oil mill fungi. The fungi was isolated and identified as Trichoderma sp. Lipolytic activity of Trichoderma sp. was preliminarily confirmed by Rhodamine B method, lipase production was carried out using mineral medium. The extracellular protein concentration and lipase enzyme activity (7.83U/ml) was maximum at 4th day of incubation period. Trichoderma sp. was studied by using different carbon, oil and nitrogen sources. It was found that carbon, oil and nitrogen sources like glucose, groundnut oil and sodium nitrate were shown the maximum lipase activity. From the ANOVA analysis, the effect of different sources on lipase production was more significant.